2019
DOI: 10.1177/2050313x19881594
|View full text |Cite
|
Sign up to set email alerts
|

The role of anti-tumour necrosis factor in wound healing: A case report of refractory ulcerated necrobiosis lipoidica treated with adalimumab and review of the literature

Abstract: Necrobiosis lipoidica is a chronic granulomatous disease historically associated with diabetes. Necrobiosis lipoidica commonly presents with erythematous papules or plaques on the anterior lower extremities, which can be ulcerated in up to 30% of patients. The pathophysiology of necrobiosis lipoidica is unknown but proposed to be predominantly linked to microangiopathy. No treatment option for necrobiosis lipoidica has shown consistent efficacy. Previous case reports have shown immune-modulating agents to be r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The obtained spheres are not able to induce inflammation or present low proinflammatory potential in the case of Kan-loaded spheres. The proinflammatory TNF-α cytokine is involved in the early process of wound healing by recruiting inflammatory cells to the site of infection and stimulating macrophage phagocytic activity [ 93 , 94 ]. Therefore, stimulation of TNF-α production by P(3HB-3HV)-CS-Neo/-Kan treatment could contribute to an enhancement of the wound healing process, where increased levels of TNF-α are imperative for proper repair.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained spheres are not able to induce inflammation or present low proinflammatory potential in the case of Kan-loaded spheres. The proinflammatory TNF-α cytokine is involved in the early process of wound healing by recruiting inflammatory cells to the site of infection and stimulating macrophage phagocytic activity [ 93 , 94 ]. Therefore, stimulation of TNF-α production by P(3HB-3HV)-CS-Neo/-Kan treatment could contribute to an enhancement of the wound healing process, where increased levels of TNF-α are imperative for proper repair.…”
Section: Resultsmentioning
confidence: 99%
“…Basoulis et al. and Sandhu et al 18,19 . demonstrated two patients who did not relapse after discontinuing biological agent therapy.…”
Section: Discussionmentioning
confidence: 98%
“…Basoulis et al and Sandhu et al18,19 demonstrated two patients who did not relapse after discontinuing biological agent therapy.Evidence for topical calcineurin inhibitors in the treatment of NL has been described in case reports since 2004 20. Our review highlights existing case reports and a single multicenter study supporting the use of calcineurin inhibitors.…”
mentioning
confidence: 99%
“…In addition, it is important to know that GLUT-1 is also dependent on the levels of various growth factors, which increase when insulin levels are high [ 28 ]. This could also explain the efficacy of TNF-α inhibitor drugs in NL [ 29 ].…”
Section: Etiopathogenesismentioning
confidence: 99%